Activities of the Tashkent Scientific School of Anthropology in the Study of the Racial Character of the Population of Central Asia - Sulaimanov Amaliddin Nurbaevich (Zien Journals, 2022)
It is considered in the present article the historiography of research of Tashkents anthropological research school on learning anthropology and ethnic history of nations of Central Asia in 1920-1960 years of XX century
Keywords: Antropology; ethnic; Khorezm; Bactria